An intervention model for developing self-directed learning skills in NEET-youth: a literature review - Kõiv, Kerli; Saks, Katrin; Gencel, Ilke Evin; Güven, Kaan M.; Azzopardi, Abraham; Todoroska, Valentina; Petkovska, Elena (Frontiers in Education, 2024)
In response to the growing need for self-directed learning (SDL) skills in a rapidly changing world, research was conducted to map interventions that support SDL skills, aiming to find a model for supporting SDL skills in NEET-youth. SDL competencies support continuous personal development and coping with change.There is a significant number of young people in society who do not participate in working life, education, or training (NEET-youth) and are characterised by a low level of education. Little has been done to support SDL skills interventions for them; however, bringing young people back to the education path is a crucial issue. This raises important questions about which supportive approach and tools are most beneficial for developing SDL skills in NEET-youth, and how best to implement them. This literature review is based on the analysis of 25 articles. The results of the study showed that SDL interventions have not been used for NEET-youth, and therefore, the new model was created. In the case of NEET-youth the SDL intervention should be seen as a non-formal learning process that combines various activities that enable self-reflection and real-life experiences for acquiring new positive learning experiences.